Modelling the cancer growth process by Stochastic Differential Equations with the effect of Chondroitin Sulfate (CS) as anticancer therapeutics - Mazlan, Mazma Syahidatul Ayuni; Rosli, Norhayati; Ichwan, Solachuddin Jauhari Arief; Azmi, Nina Suhaity (IOP Publishing Ltd, 2017)
A stochastic model is introduced to describe the growth of cancer affected by anti- cancer therapeutics of Chondroitin Sulfate (CS). The parameters values of the stochastic model are estimated via maximum likelihood function. The numerical method of Euler-Maruyama will be employed to solve the model numerically. The efficiency of the stochastic model is measured by comparing the simulated result with the experimental data.